2008
DOI: 10.1080/10641260701686846
|View full text |Cite
|
Sign up to set email alerts
|

Diet, Abundance, and Distribution as Indices of Turbot (Psetta maximaL.) Release Habitat Suitability

Abstract: Selection of a suitable release habitat is critical for stock enhancement. As part of the Danish turbot stock enhancement program, individually tagged, artificially reared juveniles were released into three different habitats. Data from the recaptures in the following year revealed a significant effect of release habitat on turbot growth. This raised the question whether such differences in growth could have been predicted before the release by comparing easily measurable characteristics of wild turbot caught … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 32 publications
0
18
0
Order By: Relevance
“…The proportion of prey fishes in the diet increased and that of prey mysids decreased concomitantly with the passage of time after release or with the body size increase, indicating the higher efficiency of piscivory for energy gain. The prompt shift of their diet to fishes might be advantageous for efficient feeding and subsequent growth, as reported for turbot Psetta maxima (L. 1758) (Sparrevohn & Støttrup, 2008), but the diet shift is not thought to be critically important. The recovery in K r of HR P. olivaceus indicates sufficient prey availability even if they consume only mysids.…”
Section: Discussionmentioning
confidence: 96%
“…The proportion of prey fishes in the diet increased and that of prey mysids decreased concomitantly with the passage of time after release or with the body size increase, indicating the higher efficiency of piscivory for energy gain. The prompt shift of their diet to fishes might be advantageous for efficient feeding and subsequent growth, as reported for turbot Psetta maxima (L. 1758) (Sparrevohn & Støttrup, 2008), but the diet shift is not thought to be critically important. The recovery in K r of HR P. olivaceus indicates sufficient prey availability even if they consume only mysids.…”
Section: Discussionmentioning
confidence: 96%
“…Furthermore, they act as a food source for other juvenile fishes in the area such as G . morhua (Fjøsne & Gjøsæter, ) and turbot Scophthalmus maximus (L. 1758) (Sparrevohn & Støttrup, ; Florin & Lavados, ). Ammodytids are the main prey of juvenile M .…”
Section: Discussionmentioning
confidence: 99%
“…Støttrup et al (2002) even reported faster growth of hatchery-reared animals during the first season after release, probably due to their better initial body condition. Variability in growth of released fishes was partially dependant on habitat suitability (Sparrevohn and Støttrup 2008). Andersen et al (2005) also reported strong effects of the quality of the release habitat (e.g.…”
Section: Performance Of Domesticated Flatfish In the Wildmentioning
confidence: 97%